The double-edged sword: increased hemolysis following the addition of an oxygenator to the Berlin heart for respiratory support - Hakami, Emad A.; Beheri, Reem M.; Albert, Dimpna C.; Alsomali, Ahlam H.; Tsai, Felix W. (International Journal of Contemporary Pediatrics, 2025)
Integrating oxygenators into Berlin heart ventricular assist devices (VADs) for pediatric patients with heart failure and respiratory compromise can be lifesaving but may lead to significant complications, including increased hemolysis. We present two pediatric cases that highlight the challenges of oxygenator use in Berlin heart VADs, focusing on hemolysis, clinical interventions, and patient outcomes. In both cases, the integration of an oxygenator resulted in elevated plasma-free hemoglobin and bilirubin levels, indicative of hemolysis. Following the removal of the oxygenator, these laboratory abnormalities resolved, and clinical status improved. These cases underscore the potential risks associated with oxygenator integration into Berlin Heart VAD circuits and emphasize the importance of close monitoring, timely recognition of hemolysis, and individualized decision-making regarding the duration of oxygenator use.